Elastic micro-strain energy at the austenite-twinned martensite interface (Archives of Mechanics - Test, 2005)
A micromechanical scheme is developed for the analysis of elastic micro-strains induced by local incompatibilities at the austenite-twinned martensite interface. The aim of the paper is to estimate the elastic micro-strain energy which is an important factor in the formation of microstructures during the martensitic transformation. The finite deformation framework is applied, consistent with the crystallographic theory of martensite, and full account is taken for elastic anisotropy of the phases. As an example, the microstructures in the cubic-to-orthorhombic transformation in CuAlNi shape memory alloy are analyzed by the finite element method for the assumed class of zigzag shapes of the austenite-martensite interface at the micro-level. Finally, the effect of the interphase boundary energy on the microstructure of the transition layer is studied.